Cutaneous leishmaniasis caused by Leishmania donovani in the tribal population of the Agasthyamala Biosphere Reserve forest, Western Ghats, Kerala, India. Issue 2 (February 2015) - Kumar, N. Pradeep; Srinivasan, R.; Anish, T. S.; Nandakumar, G.; Jambulingam, P.
Abstract : Cutaneous leishmaniasis (CL), a neglected tropical disease, is reported to be prevalent in tribal villages located in the Agasthyamala Biosphere Reserve forests of Western Ghats, Kerala state, India. We carried out an investigation to characterize the species of Leishmania parasites involved in these infections prevalent among one of the oldest human tribal populations in India. Skin aspirates collected from 13 clinically diagnosed cases were subjected to histopathological investigations, serological rapid tests using 'rk39' and molecular diagnostics. Clinical manifestations recorded among the patients were hypo-pigmented erythematous nodules/papules on limbs and other parts of the body. Histopathological investigations of these skin lesions among patients showed Leishman–Donovan bodies in macrophages. None of the patients were found to be positive for rk39 tests, which detect active visceral leishmaniasis. Using three different genetic markers [kinetoplast minicircle DNA, 3′ UTR region of heat-shock protein 70 (Hsp70) and Hsp70 gene] we identified the parasite species involved in these infections to be Leishmania donovani . The 6-phosphogluconate (6-PGDH) gene sequences of the parasite isolates from Western Ghats indicated close genetic relatedness to L. donovani isolates reported from Sri Lanka, also causing CL. This could be cited as another instance of 'local endemism' of organisms in this single 'bio-geographic unit'. Abbreviations: CL, cutaneous leishmaniasis; k-DNA, kinetoplast DNA; LD, Leishman–Donovan; VL, visceral leishmaniasis.